Histochemical Effect of Capsaicin Alone or in Combination with The Metformin on Ovaries Structure After Induced a Polycystic Ovary Syndrome by Letrozole in Rats - Alia Mohammed Khudier, Karim H. Al-derawi, Labeed A. Al- saad (Basrah Journal of Veterinary Research)
The current study, we investigated the effect of capsaicin alone or combined with metformin on induced polycystic ovary syndrome in rat adult females. The total number of animals was used (70). The study was divided into two experiments: The first experiment was to induce polycystic ovary syndrome in (50) animals were divided as follows: GI (n= 10) (CMC) served as a control group. The reminder (n = 40) GII were given Letrozole 1 mg\kg. The duration of this experiment continued (21 day). At the end of experiment, (n=10) females that received letrozole were scarified and considered as (PCOS subgroup). The GI (n=10) CMC were also scarified to ensured PCOS accrued. For histochemical analysis, the ovaries of female rats were isolated and fixed in a formalin solution 10%. In a second experiment, the reminder of female rats from first experiments GII (PCOS group n=30) divided into three subgroups (10 animals/subgroup: (Capsaicin + letrozole) subgroup, was given 0.5 mg/kg of capsaicin, (metformin) subgroup was given metformin 9 mg\ kg and (metformin + capsaicin + letrozole) subgroup. The remainder of the total number of animals studied (n = 20) (PCOS not induced) were divided into (10 animals/subgroup) (alcohol subgroup) as control group that was given 0.5 ml from alcohol and (capsaicin) without induction of polycystic ovary syndrome as a positive control subgroup, was given capsaicin (0.5 mg/ kg). The second experiment continued for 21-days after the end of the experiment. All animals were sacrificed and the ovaries were removed, fixed (10% buffered formalin), and prepared for histochemical study using Mallory's trichrome stain. The study, we recorded multiple cysts, bleeding and mucin in the PCOS subgroup compared with the CMC group. Histochemical examinations of the treated subgroups with capsaicin alone or with metformin showed an improvement in ovarian tissue, disappearance of cysts and bleeding compared with the control groups and the PCOS subgroup. We thought that capsaicin alone or in combination with metformin showed an improvement in ovarian tissue.